Factors Influencing Satisfaction, Perceived Disability and Handicap among Hearing Aid Users in the Turkish Population - Karabulut, Esma Çağal; Karabulut, Mustafa; Kirazlı, Gülce; Akmeşe, Pelin Piştav (ENT Updates, 2025)
Background: To examine factors influencing satisfaction, perceived disability and handicap and to investigate whether satisfaction correlates with perceived disability and handicap among hearing aid (HA) users in the Turkish population. Methods: A prospective cross-sectional study involving 133 patients using unilateral or bilateral HAs was conducted. Data on demographic factors, including age, gender, socioeconomic status, degree of hearing loss, HA experience, HA fitting side, daily HA usage, and HA style were collected. Satisfaction, perceived disability and handicap were assessed using the Abbreviated Profile of Hearing Aid Benefit and the Amsterdam Inventory for Auditory Disability and Handicap (AIADH), respectively. Multiple linear regression analysis was performed to examine factors influencing satisfaction, perceived disability and handicap. Pearson correlation test was used to assess the correlation of satisfaction with perceived disability and handicap. Results: Age, degree of hearing loss, and HA side were significant predictors of APHAB satisfaction scores, while only degree of hearing loss predicted AIADH scores (p < 0.05). Gender and HA experience did not consistently predict outcomes (p > 0.05). A weak negative correlation was obtained between APHAB satisfaction scores and the AIADH disability scores among HA users (p < 0.05; r: −0.390). Conclusion: The study highlights age, degree of hearing loss, and HA side as predictive factors for HA satisfaction. Furthermore,the degree of hearing loss influences perceived disability and handicap. HA satisfaction, perceived disability and handicap did not exhibit a notable relationship among HA users. These findings underscore the importance of healthcare professionals in addressing the specific needs of individuals with HA users to enhance their overall quality of life.